Multiderivative Combined Dissipative Compact Scheme Satisfying Geometric Conservation Law II: Applications on Complex Curvilinear Meshes (Advances in Applied Mathematics and Mechanics, 2019)
The multiderivative combined dissipative compact scheme (MDCS) is extended to implement applications on complex curvilinear meshes. According to our previous evaluation on the scheme, a fifth-order MDCS, which has coexistent superior resolution power and relatively high efficiency, is chosen to present the performance of the MDCS. The capability of the fifth-order MDCS is evaluated by increasingly complex meshes in three typical tests: acoustic scattering from two cylinders, flow over a rod-airfoil configuration and flow over a landing gear model. On the curvilinear meshes, high resolution power possessed by the representative fifth-order MDCS is demonstrated for resolving acoustic wave. Moreover, the MDCS presents promising capability in simulating multiple scales in turbulent flow.